The Effective Use of the Inexpensive LED Microscope with Rhodamine Blue Staining to Identify Microplastics. Issue 1 (16th February 2023) - Smith, C; Denaro, F; Fan, C; Pramanik, S
Abstract: Microplastics (MPs) > 5 mm (about 0.2 in) are ubiquitously found in our biosphere; however, oceans, rivers, lakes, streams, and estuary water columns are the main repository of MPs because of their light weight and movement due to wind currents. MPs are typically observed and identified using expensive instruments such as scanning electron microscopes (SEM), Fourier spectroscopy (FTIR), Raman spectroscopy, and fluorescent microscopes, all of which cost thousands of dollars. We have used inexpensive light-emitting diode (LED) microscopes to identify the presence of aquatic microplastics, with results comparable to those obtained with high-end fluorescence microscopes. The MPs examined were separated from the gelatinous body of jellyfish captured from the Patuxent River in Maryland and stained with rhodamine blue (Rhb).